2013
DOI: 10.1016/j.jpeds.2012.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone Propionate Pharmacogenetics: CYP3A4*22 Polymorphism and Pediatric Asthma Control

Abstract: Objective To determine the relationship between allelic variations in genes involved in fluticasone propionate (FP) metabolism and asthma control among children with asthma managed with inhaled FP. Study design The relationship between variability in asthma control scores and genetic variation in drug metabolism was assessed by genotyping nine single nucleotide polymorphisms (SNPs) in CYP3A4, CYP3A5, and CYP3A7. Genotype information was compared with asthma control scores (0 = well-controlled to 15 = poorly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
54
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 33 publications
2
54
0
6
Order By: Relevance
“…In support of this idea, a recent publication by Stockmann et al (2013) demonstrated that the expression of the CYP3A4*22 allele, which codes for an inactive enzyme in the liver (Elens et al, 2011a(Elens et al, ,b, 2012(Elens et al, , 2013Kitzmiller et al, 2013), coupled with treatment of these patients with the CYP3A4 and 3A5 mechanism-based inhibitor fluticasone propionate (Murai et al, 2010), correlated with improved asthma control. As such, a decrease in CYP3A-mediated metabolism of fluticasone propionate (and possibly other glucocorticoids) in the lung and liver may increase the bioavailability of the active drug in the lung, leading to greater efficacy.…”
Section: Discussionmentioning
confidence: 93%
“…In support of this idea, a recent publication by Stockmann et al (2013) demonstrated that the expression of the CYP3A4*22 allele, which codes for an inactive enzyme in the liver (Elens et al, 2011a(Elens et al, ,b, 2012(Elens et al, , 2013Kitzmiller et al, 2013), coupled with treatment of these patients with the CYP3A4 and 3A5 mechanism-based inhibitor fluticasone propionate (Murai et al, 2010), correlated with improved asthma control. As such, a decrease in CYP3A-mediated metabolism of fluticasone propionate (and possibly other glucocorticoids) in the lung and liver may increase the bioavailability of the active drug in the lung, leading to greater efficacy.…”
Section: Discussionmentioning
confidence: 93%
“…A description of the study population is provided in the online supplement. DNA was extracted as previously described (27).…”
Section: Calcium Imaging Assaysmentioning
confidence: 99%
“…Each patient's level of chronic asthma control was determined using a questionnaire (Table E2) based upon guidelines modified from the National Heart Lung and Blood Institute Expert Panel Report 3 (28) as described by Stockmann and colleagues (27). Each subject's asthma control score was calculated as the sum of all five question in Table E2, providing a score ranging from 0 (optimally controlled) to 15 (poorly controlled).…”
Section: Characterization Of Asthma Phenotypesmentioning
confidence: 99%
“…19 The CYP3A4*22 allele has a relatively high frequency, ranging from 3.2% to 6.9% in the white population. [19][20][21][22][23][24] CYP3A4*22 appears to be the most promising CYP3A4 SNP reported so far. We showed before higher serum concentrations of quetiapine, an antipsychotic mainly metabolized by CYP3A4, in carriers of the CYP3A4*22 allele.…”
mentioning
confidence: 99%
“…20,21,26 Lopinavir displayed lower clearance and higher trough concentrations in CYP3A4*22/*22 HIV-positive patients, 23 and presence of the CYP3A4*22 allele was accompanied by improved asthma control in fluticasone propionate-treated children. 22 For paclitaxel, even without an association of CYP3A4*22 with pharmacokinetic parameters, female carriers of *22 appeared to be at risk of developing grade 3 neurotoxicity, 27 a result of a decreased cytoprotective effect against toxic substrates by CYP3A4 expressed in peripheral nerves. 28 Aripiprazole, haloperidol, pimozide, and risperidone are frequently prescribed antipsychotics in the psychiatric hospital GGz Centraal located in Veldwijk, Ermelo, The Netherlands.…”
mentioning
confidence: 99%